Critiques : In Defence of Development - Brass, Tom, (Social Sciences E-Books Online, Collection 2025., 2025)
Critiques presented here in defence of development range across a number of issues, all of which are central to discussions about the desirability or undesirability of this historical process. These include one particular aspect - labour market competition - of the debate about racism, why the reproduction of this ideology is more acute at some historical conjunctures but not others, the same question that can also be asked of the industrial reserve. Equally contentious is the current dominance of populist and postmodern interpretations of rural development, in the misleading guise of new paradigms, the object of which is to exorcise two ghosts: not just development itself, but also Marxist theory about development. See Less